2007
DOI: 10.1021/cm0704682
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Morphology of Complex Semiconductor Nanocrystals with a Type II Heterojunction, Dots vs Peanuts, by Thermal Cycling

Abstract: Type II CdSe/CdTe core/shell nanocrystals with a dot shape were synthesized using a modified SILAR technique that incorporates cycling of the reaction temperature (thermal cycling). Conversely, experimental results revealed that the standard SILAR alone produced type II core/shell nanocrystals in a peanut shape (1D). Despite their differences in shape, the optical properties observed for the type II dot- and peanut-shaped core/shell nanocrystals were similar. The dot-shaped nanocrystals were confirmed as core/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 27 publications
2
103
0
Order By: Relevance
“…7 As mentioned above, attempts to generate water-soluble CdSe/ CdTe core/shell nanocrystals failed. This is probably because of the hole trapping by the negatively charged thiolate ligands bounded on the surface of the CdTe shell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 As mentioned above, attempts to generate water-soluble CdSe/ CdTe core/shell nanocrystals failed. This is probably because of the hole trapping by the negatively charged thiolate ligands bounded on the surface of the CdTe shell.…”
Section: Resultsmentioning
confidence: 99%
“…In attempts to further boost the PL QY, type-II heterojunctions were examined using both quantum dots and quantum shell nanocrystals as the starting materials for the formation of the type-II nanocrystals, each of which was tested with a variety of shell thicknesses and sizes. 7 In all of these attempts, one interesting point is that straight SILAR always ended up either with minimum growth of the shell or forming peanut-shaped heterojunction nanocrystals, and SILAR-TC yielded the type-II core/shell dots or core/shell/shell type-I/type-II dots. Unfortunately, 30% PL QY was about the highest for stable dots, however up to 50% PL QY was observed for unstable ones.…”
Section: Introductionmentioning
confidence: 99%
“…It could be seen that the three prepared QDs probes had different particle sizes, 4.5 nm for probe A, 2.9 nm for probe B, and 3.1 nm for probe C, and they dispersed well. Moreover, the morphologies of the three QDs probes were of dot-shaped heteronanostructures, which was a benefit for the high-fluorescence quantum yields in aqueous media (Blackman et al 2008;Blackman et al 2007;Gui and An 2013). In the high-resolution TEM images of the three QDs probes, it could be found that the crystal lattice of probe A was more clear than that of probes B and C, suggesting that in the preparation of probes B and C, the long carbon chain affected the crystallinity of the CdTe/CdS QDs, which was consistent with the XRD analysis results.…”
Section: Characterization Results Of Prepared Qds Probesmentioning
confidence: 99%
“…Orange-colored CdSe QDs were used as core for synthesizing the core-shell QDs according to the modified SILAR procedure [16,17] and the modified TOP-assisted method [21].…”
Section: Synthesis Of Cdse/zns Core-shell Qds Based On Different Procmentioning
confidence: 99%
“…In particular, successive ionic layer adsorption and reaction (SILAR) is the most widely used method [7,16,17]. However, the intrinsic strain-induced formation of misfit dislocations and the defects within the shell cannot be avoided by SILAR method, which results in the decrease of QY as the shell thickness increasing [6,8,18].…”
Section: Introductionmentioning
confidence: 99%